A Curation Activity-Based Self-Regulated Learning Promotion Approach as Scaffolding to Improving Learners' Performance in STEM Courses. (July 2022) - Wang, Qi; Peng, Yan; Wang, Huimin
Self-regulated learning (SRL) is an important method in STEM courses that can help learners acquire knowledge by discovering, organizing, and integrating materials. However, learners may not perform well without scaffolding, which results in purely participation in tasks without solid knowledge acquisition. To guarantee SRL effectiveness, scaffolding that can support learners' knowledge discovery, organization and integration is needed when curation is introduced to support high-level cognition in STEM courses focusing on these facets. The researchers analyzed the advantages and procedures of curation and developed a curation tool and a curation activity-based SRL mode. To verify the effects of the proposed tool and mode, 64 Grade 7 students were involved and assigned to the experimental and control groups and learned with specific tasks. The results revealed that the experimental group showed interest in the mode and achieved better learning outcomes. Learners in the experimental group also submitted higher-quality practical work that demonstrated the effectiveness of the mode. Moreover, this approach promoted deep thinking without increasing the learners' cognitive load. Finally, this study provided an innovative scaffolding tool and mode for SRL that leveraged learners' knowledge acquisition and task completion. This idea has positive implications for future SRL research.